Análisis del área foliar del alcornoque en relación con tratamientos silvo-pastorales - Caritat, A. I.; Molinas, M. I.; Vilar, I. P.; Masson, L. (Scientia gerundensis, 1999)
The fluctuations showed by ecophysiologic parameters, like leaf area and leaf area indices, in relation to silvo-pastoral treatments can be used to evaluate the effects of these treatments on o&-cork forests. Leaf area shows a close relation to production and is a good indicator of the physiological state of the plants. Leaf area, leaf area indices and specific leaf weight have been studied in four cork-oak wood stations in relation to shrub clearing and grazing treat- ments. Leaf parameters have been measured using a computer image analysis system. We found that, in general, leaf average area is increased by silvo-pastotal treatments, apparently in order to recover the wasted canopy and in answer to nutrient supply. On the other hand, leaf area index decreases after treatments because of the leaf biomass lost, but the fast apical growth showed by cork-trees in treated plots points to a quick recovery of this parameter when an appropiate tree density is reached.
Keywords: cork-oak; Grazing; leaf area; leaf index; shrub cleareing; silvo-pastoral treatments